Turismo e meio ambiente: da inserção dos resorts à (in) sustentável gestão ambiental no Porto das Dunas, Aquiraz/CE - Rodrigues, Frederico do Nascimento (2016)
This research is analysis of coastal tourism that focuses on one of Brazil's northeastern beaches located in the state of Ceará Porto das Dunas in Aquiraz municipality that integrates the Metropolitan Region of Fortaleza capital since its crystallization in 1973 It is understood that the tourism is in a fine line with the environment thus it was observed that the 1990s was the cornerstone in this process due to the Eco-92 held in Rio de Janeiro where he discussed the importance of sustainable development In this context the research had the main objective to understand the insertion of the resorts in the aforementioned beach and sustainability initiatives developed by enterprises in partnership with the Porto das Dunas Residents Association To achieve the proposed objectives we carried out a diachronic study of space bibliographic research field work interviews mapping journal research technical visits to resorts and state agencies Here we define the actions of sustainability eco-sustainable actions because it was found in the field that they begin if not for an environmental awareness taken but by an economic rationality followed by an environmental sensitivity It was noticed that in the first instance the projects sought to ease spending in three specific fields solid waste management energy and water consumption In developing an Environmental Management System - EMS these companies realized how much they could save by implementing an environmental management Thus also starts up an environmental sensitivity of the area where they live the coast These enterprises adopt green discourse as ideology thus decreasing the energy and water consumption through the management of solid waste is carried out now discharges properly where the final destination is not the landfills for now all waste is reused water buoys remains turned into sandals by Melissa company PET bottles transformam- in plumbing materials food scraps saw organic fertilizer wastewater is treated and reused for gardening in the projects Note to sustainable discourse that builds positive image of the resorts presenting itself as the tourism marketing of the twenty-first century however it was realized that the environment also benefits because it was noted that the impacts are being mitigated companies undergo transmutation phase no longer polluting potential and become friendly green